Penelitian kelompok: Model permainan sebagai alternatif untuk pemanasan siswa - Samodra, Y Tovan Juni; Gustian, Uray; Astiati; Supianto; Susanto, Imam Andi; Riduansyah; Suhendra, Agito Fredi (Edu Sportivo: Indonesian Journal of Physical Education, 2022)
The background of this research is that the warm-up for sports or physical education is always done by running around the field. The essence of warming up attempts to prepare physiologically and psychologically to be ready for higher activities. This research has made a real contribution to the development of warm-up activities, which were previously carried out by simply running around the field. The purpose of this research is to produce several game models that can be used as an alternative for warming up. The research design uses development research in sequence, problem exploration, design preparation, expert trials, student trials, small-scale trials, large-scale trials. The design was consulted with physical education lecturers and teachers, student trials were conducted on sports coaching education students, small-scale trials were conducted on sports coaching students, large-scale trials were conducted on elementary and junior high school students. Five types of heating were developed, and the achievement of the heating results was measured by pulse. Data were analyzed by descriptive statistics. The results of the study, five game designs were arranged (1,2,3,4 and 5), the results of small-scale trials stated that the pulse had entered the exercise pulse. Tests on students mean that all games have reached the pulse of practice. It was concluded that these five games based on a series of trials were declared feasible and could be used for warm-up activities.